ASPECTS OF THE DEVELOPMENT OF THE PREFECTURE OF ELBASAN (ALBANIAN PREFECTURE) IN THE ALBANIAN MONARCHY (1928-1939) - Mita, Rudina; Lumi, Elvira (European Scientific Journal, ESJ, 2015)
We Albanian Monarchy years (1928-1939) Elbasan in accordance with the policies of the Central Government made important steps in the evolution and development in the prefecture. What is notable not only evidenced in Elbasan but also in its sub-prefectures and municipalities during 1928-1939 were efforts, dogged persistence and determination of elbasanasve to separate the east and to embrace the western way of progress, it not only as a concept but the complexity of it (policy reforms). Among the aspects of life to progress on the Albanian Monarchy period Elbasan Prefecture mention: progress in the field of education, which consisted in the opening of schools, teacher preparation staff, drafting of texts and the fight against illiteracy; the humanity expressed in the support and contribution in cash that the population of this area given to national education; development of infrastructure (roads, bridges); The first steps of progress in the industry (factories before the domestic capital); in the cultural field (creation of the Cultural Society "Kristoforidhi", opening the Library Qemal Baholli etc.); social emancipation (branch of the Society "Albanian woman" in Elbasan, reform on the woman's face detection) and in an active political life.